Drug-Induced Osteoporosis - Vinall, Phil (MD Conference Express, 2008)
This article discusses various drug therapies that may induce osteoporosis in some patients. These treatments include not only corticosteroids (glucocorticoid), DMARDs, and NSAIDs, as well as recent data where osteoporosis is induced by adjuvant antineoplastic treatment in pre- and postmenopausal women with early breast cancer and by androgen deprivation therapy in men who are being treated for prostate cancer.